A critical overview of emotion processing assessment in non-affective and affective psychoses - Irene Gorrino; Maria Gloria Rossetti; Francesca Girelli; Marcella Bellani; Cinzia Perlini; Giulia Mattavelli (Cambridge University Press, 2024)
Abstract Aims Patients with affective and non-affective psychoses show impairments in both the identification and discrimination of facial affect, which can significantly reduce their quality of life. The aim of this commentary is to present the strengths and weaknesses of the available instruments for a more careful evaluation of different stages of emotion processing in clinical and experimental studies on patients with non-affective and affective psychoses. Methods We reviewed the existing literature to identify different tests used to assess the ability to recognise (e.g. Ekman 60-Faces Test, Facial Emotion Identification Test and Penn Emotion Recognition Test) and to discriminate emotions (e.g. Face Emotion Discrimination Test and Emotion Differentiation Task). Results The current literature revealed that few studies combine instruments to differentiate between different levels of emotion processing disorders. The lack of comprehensive instruments that integrate emotion recognition and discrimination assessments prevents a full understanding of patients' conditions. Conclusions This commentary underlines the need for a detailed evaluation of emotion processing ability in patients with non-affective and affective psychoses, to characterise the disorder at early phases from the onset of the disease and to design rehabilitation treatments.